2020
DOI: 10.1101/2020.01.05.893529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Derived ecological niches of indoor microbes are crucial for asthma symptoms in university dormitories

Abstract: Increasing evidences from home environment indicate that microbiome community is associated with asthma. However, indoor microbiome composition can be highly diverse and dynamic, and thus current studies fail to produce consistent association. Chinese university dormitories are special high-density dwellings with a standard built environment and personal characteristics for occupants, which can be used to disentangle the complex interactions between microbes, environmental characteristics and asthma.Settled ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…According to Fu et al (2020a), the bacterial phylum Actinobacteriota was found to be protectively associated with respiratory infections among students. A few other studies also reported that taxa richness and abundance of Actinobacteria were protectively associated with childhood asthma (Karvonen et al, 2019;O'Connor et al, 2018) and asthma symptoms among university students (Fu et al, 2020b). This contradicts our findings as we found Actinobacteria to be positively associated with increased risk of LRTI among under-five children.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Fu et al (2020a), the bacterial phylum Actinobacteriota was found to be protectively associated with respiratory infections among students. A few other studies also reported that taxa richness and abundance of Actinobacteria were protectively associated with childhood asthma (Karvonen et al, 2019;O'Connor et al, 2018) and asthma symptoms among university students (Fu et al, 2020b). This contradicts our findings as we found Actinobacteria to be positively associated with increased risk of LRTI among under-five children.…”
Section: Discussioncontrasting
confidence: 99%
“…Two indoor microbiome studies reported that taxa from Actinobacteria were mainly protective for childhood asthma 36,51 . Our previous study showed that taxa richness and abundance in Actinobacteria were protectively associated with asthma symptoms 52 . Actinobacteria is a diverse class of bacteria, which widely distributed in various terrestrial and aquatic environments 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Their framework draws attention to causal relationships between microbial characteristics, environmental dynamics, and cumulative ecosystems processes with the potential to incorporate relevant mechanistic links into predictive ecosystem models. A powerful element of the Hall et al ( 6 ) framework is that it applies to diverse systems spanning natural ( 7 ), host-associated ( 8 ), and built ( 9 ) environments as well as across spatiotemporal scales ( 10 ). While potentially very useful, the Hall et al ( 6 ) framework has seen little direct use in terms of explicitly defining and evaluating the linkages within specific study systems (but see 3 ).…”
Section: Introductionmentioning
confidence: 99%